Pengaruh Kemampuan Manajerial Pimpinan dan Perilaku Inovatif Terhadap Kinerja Pegawai Dinas Pariwisata dan Ekonomi Kreatif Kabupaten Kolaka Timur - Munajira Munajira; Niar Astaginy; Hendrik Hendrik (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to find out: The Effect of Leadership Managerial Ability and Innovative Behavior on Employee Performance at the Tourism and Creative Economy Office of East Kolaka Regency. This research uses an approach with quantitative methods. Data collection in this study used observation, documentation and questionnaires. The population in this study is all employees of the Koltim Tourism and Creative Economy Office. While the sample of this study amounted to 34 employees by determining samples using census techniques. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model test (outer model) and structural model testing (inner model) with Smart-PLS 4.0. Based on the results of the study, it is known that the variable of Managerial Ability of Leaders has a positive and significant effect on Employee Performance which is indicated by a P-Value value of 0.011. As well as the variable Innovative Behavior has a positive and significant effect on Employee Performance, this is indicated by a P-Value value of 0.000.